DEFECTS OF THE MONTHLY PROFIT AND LOSS STATEMENT. - Castenrolz, W. B. (The Accounting Review, 1926)
Abstract This article focuses on the defects of monthly profit and loss statement. Accountants have consistently advocated the advantages which accrue to a business through the preparation and use of monthly operating statements, based upon the inclusion each month of all presumably applicable expenses, and upon the use of perpetual inventories. But, in his zeal to have such statements, the accountant's logic has not traveled the entire distance, with the result that the average monthly profit and loss statement, especially in manufacturing industries, remains quite illogical and meaningless. Because of the perpetual inventory control and adequate cost accounting system available, the cost of sales account and the gross profit, as reflected in the typical statement, may be regarded as adequate and as expressive of the facts which influence and determine them. Beyond the gross profit, however, the monthly profit and loss statement is quite inane, thus indicating a considerable mental prolepses in the field of analytical and constructive accounting. Much credit, of course, is due those who have developed factory cost and commercial accounting so that the cost of sales account does properly indicate the manufacturing cost or the purchase cost respectively of the commodities sold. The costs of sales, obviously, automatically varies with the volume of sales wherever a cost system is present. Cost accounting, in a sense, is a process of building up values which are expressed in finished product inventory accounts and in goods in process inventories.